HVR-1 Sequence Analysis of Malay Population of Peninsular Malaysia - Muhamad, Ayu Suzailiana (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2007)
Sequence of hypervariable 1 (HVS-1) region was analyzed in 37 unrelated Malay population of Peninsular Malaysia. Buccal cell samples were collected from Universiti Sains Malaysia students that came from various parts of Peninsular Malaysia. A 380 bp fragment of HVS-1 region was amplified using a set of primer, HVA 1 and HVB1. Agarose gel electrophoresis was carried to examine the Polymerase Chain Reaction (PCR) product and the product was then purified prior to sequencing using QIAquick PCR Purification kit (QIAGEN). From the total of 37 samples sent for sequencing, only 25 samples were successfully sequenced. The sequence for each sample was compared to the Anderson reference sequence which act as a reference sequence to report for polymorphism; including total of polymorphic site counted, haplotypes and haplogroup. From result obtained, 52% of the samples were classified under haplogroup M, 24% were classified under haplogroup F, 16% were classified under haplogroup B and another 8% were classified under other haplogroups. This result support the finding reported by other researchers (Schurr and Wallace, 2002; Ballinger eta/., 1992).